MAKROZOOBENTHOS PADA KAWASAN KONSERVASI MANGROVE MAMBURUNGAN KOTA TARAKAN - Laga, Asbar; Firdaus, Muhammad; Agustina, Agustina (Jurnal Harpodon Borneo, 2010)
Mangrove forest in mamburungan conservation area is uniqe ecosystem, its have much biodiversity in flora and fauna. In the presence biota water especially makrozoobenthos has to big play a part in ecosystem balance. The Purpose of this  research know makrozoobenthos's relationship picture to in the presence area mangrove ecological. The research found that on four sasiun researces are 263 consisting of species 163 specieses of Gastropoda's classes, 50 specieses of Bivalva's classes, 29 specieses of Polychaetha's classes, and 21 specieses of Crustacea's classes. Variety index point (H’) one that acquired ranging among 1,60 – 2,11. Coronet density correlation adjures with found makrozoobenthos existence on Mangrove Mamburungan's conservation area is gotten assesses r s  0,6. It means to exist relationship among coronet density adjures with makrozoobenthos's existence, but don't happen perfect relationship. Key word:   Makrozoobenthos, Correlation / Relationship, Mangrove .